2011
DOI: 10.1175/2011jcli3966.1
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric Climate Change Detection by Radio Occultation Data Using a Fingerprinting Method

Abstract: The detection of climate change signals in rather short satellite datasets is a challenging task in climate research and requires high-quality data with good error characterization. Global Navigation Satellite System (GNSS) radio occultation (RO) provides a novel record of high-quality measurements of atmospheric parameters of the upper-troposphere-lower-stratosphere (UTLS) region. Because of characteristics such as long-term stability, self calibration, and a very good height resolution, RO data are well suit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
51
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
2
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 61 publications
(55 citation statements)
references
References 56 publications
2
51
0
2
Order By: Relevance
“…Furthermore, geopotential height change (m decade −1 ) relates to relative pressure change (% decade −1 ) via the atmospheric scale height by a factor of about 70 m % −1 (e.g. Leroy et al, 2006b;Scherllin-Pirscher et al, 2011b) so that expected climate change signals in geopotential height of roughly 10 m decade −1 at low to mid latitudes (Leroy et al, 2006b;Lackner et al, 2011) suggest a stability requirement like 4 m decade −1 , and correspondingly of 0.06 % decade −1 for pressure, to be reasonable values.…”
Section: Mean Trends and Structural Uncertaintymentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, geopotential height change (m decade −1 ) relates to relative pressure change (% decade −1 ) via the atmospheric scale height by a factor of about 70 m % −1 (e.g. Leroy et al, 2006b;Scherllin-Pirscher et al, 2011b) so that expected climate change signals in geopotential height of roughly 10 m decade −1 at low to mid latitudes (Leroy et al, 2006b;Lackner et al, 2011) suggest a stability requirement like 4 m decade −1 , and correspondingly of 0.06 % decade −1 for pressure, to be reasonable values.…”
Section: Mean Trends and Structural Uncertaintymentioning
confidence: 99%
“…For context, Lackner et al (2011) showed in a dedicated climate change signal detection study for RO a geopotential height increase of ∼15 m decade −1 , a warming of ∼0.3 K decade −1 in the UT and a cooling of a ∼0.6 K decade −1 in the LS tropics for the period 2001 to 2010. The corresponding structural uncertainty in the tropics as found from this uncertainty study is for geopotential height <3 m decade −1 in the UTLS.…”
Section: Mean Trends and Structural Uncertaintymentioning
confidence: 99%
“…Global Navigation Satellite System (GNSS) radio occultation (RO) (Melbourne et al, 1994;Kursinski et al, 1997;Hajj et al, 2002) is a relatively new atmospheric remote sensing technique. It can deliver data traceable to the international standard of time (the SI second) and has the potential for monitoring decadal-scale climate change (Steiner et al, 2009;Scherllin-Pirscher et al, 2011b;Lackner et al, 2011) due to its unique characteristics such as high vertical resolution, high accuracy and long-term stability of its observations, as well as self-calibration capability and global coverage (Gobiet and Kirchengast, 2004;Steiner et al, 2011). Figure 1 illustrates the GPS-to-LEO occultation geometry.…”
Section: Introductionmentioning
confidence: 99%
“…These missions have demonstrated the unique properties of the GNSS RO technique, such as high vertical resolution, high accuracy, all-weather capability and global coverage (Ware et al, 1996;Gorbunov et al, 1996;Rocken et al, 1997;Leroy, 1997;Steiner et al, 1999), and long-term stability and consistency of different RO mission observations (Foelsche et al, , 2011. Therefore, GNSS RO data products (i.e., bending angle, refractivity, temperature, 10 pressure, water vapor, and ionospheric electron density profiles) have been widely used for numerical weather prediction (NWP) (e.g., Healy and Eyre, 2000;Healy and Thepaut, 2006;Aparicio and Deblonde, 2008;Cucurull and Derber, 2008;Poli et al, 2008;Huang et al, 2010;Le Marshall et al, 2010;Harnisch et al, 2013), global climate monitoring (GCM) (e.g., Steiner et al, 2001Steiner et al, , 2009Steiner et al, , 2013Schmidt et al, 2005Schmidt et al, , 2008Schmidt et al, , 2010Loescher 15 and Kirchengast, 2008;Ho et al, 2009Ho et al, , 2012Foelsche et al, 2011a;Lackner et al, 2011) and space weather research (SWR) (Anthes, 2011;Anthes et al, 2008;Arras et al, 2008;Brahmanandam et al, 2012;Pi et al, 1997;Wickert, 2004;Yue et al, 2015).…”
Section: Introductionmentioning
confidence: 99%